Assessment of nutritional status and dietary habits of children attendingthe nursery in Sanok - Mielnik, Aneta; Pac-Kożuchowska, Elżbieta (Polish Journal of Public Health, 2018)
Introduction. The state of human health largely depends on environmental factors. Nutrition as one of them is important in the earliest stages of child development. By following the principles of rational nutrition, we provide the child the necessary components that determine its growth and development. By analyzing the relationship between nutrition and health three elements should be taken into account: selection of food, compliance with dietary guidelines and an assessment of the effects of nutrition.Aim. The research aimed at the assessment of nutritional status and dietary habits of children attending the nursery.Material and methods. The study was conducted among 92 healthy children aged 10-55 months attending two nurseries in the town of Sanok. In all the children, body mass and height were measured and the values obtained were related to the percentile charts. There was also an original questionnaire survey performed addressed to mothers of the children. It provided information on the diets of infants and introducing new complementary products to the diet of children in the first year of life. The results were compared with the nutritional standards for children fed both naturally and artificially.Results and conclusions. While assessing the nutritional status of children, it was found that incorrect body mass concerned often overweight and obesity. Mothers too early stopped breast-feeding and introduced formulas to the diet of children. The main food product that caused allergic symptoms of children was cow’s milk and its products. Most mothers preparing meals for the children used the prepared food products for infants. On the basis of the obtained results it can be concluded that the introduction of complementary food into the diet of infants in the majority did not meet current dietary recommendations in 2007. There is a need to take preventive measures carried out by medical personnel addressed to parents/carers on the proper nutrition of their children in the first years of life.